PETROGENETIC SIGNIFICANCE OF SPINELS FROM SERPENTINISED PERIDOTITES FROM THE VERIANAOUSA OPHIOLITE - Rogkala, A.; Petrounias, P.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2016)
The Veria-Naousa ophiolitic complex represents a dismembered ophiolite unit, which is superimposed on a basement consisting of rocks belonging to the Pelagonian and Axios (Almopias subzone) isopic zones in northern Greece. Mantle peridotites are composed of variably serpentinised lherzolite and harzburgite intruded by a sparse network of pyroxenitic dykes. The serpentinised lherzolite and harzburgite contain Alspinels (Cr#=38.83-42.52 and Mg#=58.94-64.77), Cr-spinels (Cr#=43.37-64.92 and Mg#=49.20-58.66) and magnesiochromites (Cr#=53.93 57.13 and Mg#=55.73- 61.71). All of them display commonly richer-in-Cr cores rimmed by secondary ferrian chromite and magnetite. Whole-rock geochemicall compositions and primary spinel chemical composition of these peridotites are analogous to peridotites that formed in a suprasubduction zone. Ιt is supported that the Mantle peridotites of the VeriaNaousa ophiolitic complex formed in a back-arc basin